2017
DOI: 10.1002/pc.24452
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and viscoelastic study of functionalized MWCNTs/epoxy/Kevlar composites

Abstract: Nanomaterials‐strengthened diglycidyl ether of bisphenol A (DGEBA) epoxy resin and aramid fiber composites were investigated for 0.16 wt% and 0.32 wt% of industrial and COOH‐functionalized multiwalled carbon nanotubes (MWCNTs). Epoxy/Kevlar fiber/MWCNT hybrid composites were prepared using a vacuum resin‐infusion molding method (VRIM) based on 0.68 aramid fiber mass fractions. The effects of MWCNTs on the viscoelastic, mechanical, and thermal properties of composites were investigated. The chemical structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Surprisingly, the three times higher content of this organoclay in the epoxy matrix did not affects the change of this parameter. In comparison with the results of other authors concerning nanoclay [ 20 , 39 ] and other nanofillers [ 25 ], the obtained change was very pronounced, which may be related to the significant interlayer distance (d-spacing) of organoclay after modification and their proper dispersion in the epoxy matrix, particularly 3 wt.%, confirmed by the SEM analysis of the brittle fracture morphology of the composite.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Surprisingly, the three times higher content of this organoclay in the epoxy matrix did not affects the change of this parameter. In comparison with the results of other authors concerning nanoclay [ 20 , 39 ] and other nanofillers [ 25 ], the obtained change was very pronounced, which may be related to the significant interlayer distance (d-spacing) of organoclay after modification and their proper dispersion in the epoxy matrix, particularly 3 wt.%, confirmed by the SEM analysis of the brittle fracture morphology of the composite.…”
Section: Resultssupporting
confidence: 64%
“…The Kevlar/epoxy composites with 0.5 wt.% MWCNTs exhibited improvements of 6%, 20%, 27%, and 48% in the tensile strength, Young’s modulus, flexural strength, and flexural modulus, respectively [ 24 ]. In turn, the authors of [ 25 ] modified the epoxy matrix in a seven-layer composite reinforced with weave aramid fabric using non-functionalized MWCNTs and -COOH functionalized MWCNTs. The described results showed that the addition of 0.32 wt.% MWCNTs with -COOH groups caused the highest increase of the thermal stability, tensile strength, and Young’s modulus of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect was also observed in nanocomposites with epoxy matrix filled with CNTs [29]. However, at higher content than 0.25 wt% of MWCNTs, the tensile strength and energy at break tended to decrease, which is probably due to agglomeration of the filler at this higher content, resulting in weak matrix-filler interfacial interaction [25]. The highest tensile strength obtained from this nanocomposite laminate filled with 0.25 wt% MWCNTs was higher than those of other composites reported in literature, for example, epoxy/Kevlar fiber filled with 0.5 wt% long length MWCNTs having 351 MPa [30] and epoxy/Kevlar filled with 0.32 wt% MWCNTs having 421 MPa [31].…”
Section: Tensile Properties Of Nanocomposite Laminatesmentioning
confidence: 63%
“…The ballistic limit is defined as an average of six impact velocities; three impact velocities resulted in partial and three impact velocities resulted in complete penetration. For prediction of ballistic limit (V 50 ) using simulation method according to the MIL-STD-662F standard [25], the ballistic helmet was subjected to fragment simulating projectile (FSP) made of steel AISI4340, with weight of 1.1 g and initial velocity of 610 m s −1 . The FSP was modeled following the Johnson-Cook model describing large strains, high strain rates and high temperature responsible for metallic materials under ballistic impact.…”
Section: Lead Corementioning
confidence: 99%
“…[ 32 ] In typical high‐temperature loading conditions, the viscoelastic response at glass transition temperatures can delay the failure time by 28.6%. [ 33 ] For the carbon/phenolic composites commonly used in solid rocket motors, it can be seen from the hot test and simulation that the structural materials of the nozzle usually bear large compression loads. Such a compression load is a thermal stress caused by the huge temperature difference inside and outside the nozzle.…”
Section: Introductionmentioning
confidence: 99%